A Global Survey on the Impact of COVID-19 on Urological Services - TANIDIR, YILÖREN (ELSEVIER, 2020)
Background: The World Health Organization (WHO) declared coronavirus disease-19 (COVID-19) as a pandemic on March 11, 2020. The impact of COVID-19 on urological services in different geographical areas is unknown. Objective: To investigate the global impact of COVID-19 on urological providers and the provision of urological patient care. Design, setting, and participants: A cross-sectional, web-based survey was conducted from March 30, 2020 to April 7, 2020. A 55-item questionnaire was developed to investigate the impact of COVID-19 on various aspects of urological services. Target respondents were practising urologists, urology trainees, and urology nurses/advanced practice providers. Outcome measurements and statistical analysis: The primary outcome was the degree of reduction in urological services, which was further stratified by the geographical location, degree of outbreak, and nature and urgency of urological conditions. The secondary outcome was the duration of delay in urological services. Results and limitations: A total of 1004 participants responded to our survey, and they were mostly based in Asia, Europe, North America, and South America. Worldwide, 41% of the respondents reported that their hospital staff members had been diagnosed with COVID-19 infection, 27% reported personnel shortage, and 26% had to be deployed to take care of COVID-19 patients. Globally, only 33% of the respondents felt that they were given adequate personal protective equipment, and many providers expressed fear of going to work (47%). It was of concerning that 13% of the respondents were advised not to wear a surgical face mask for the fear of scaring their patients, and 21% of the respondents were advised not to discuss COVID-19 issues or concerns on media. COVID-19 had a global impact on the cut-down of urological services, including outpatient clinic appointments, outpatient investigations and procedures, and urological surgeries. The degree of cut-down of urological services increased with the degree of COVID-19 outbreak. On average, 28% of outpatient clinics, 30% of outpatient investigations and procedures, and 31% of urological surgeries had a delay of >8 wk. Urological services for benign conditions were more affected than those for malignant conditions. Finally, 47% of the respondents believed that the accumulated workload could be dealt with in a timely manner after the COVID-19 outbreak, but 50% thought the postponement of urological services would affect the treatment and survival outcomes of their patients. One of the limitations of this study is that Africa, Australia, and New Zealand were under-represented. Conclusions: COVID-19 had a profound global impact on urological care and urology providers. The degree of cut-down of urological services increased with the degree of COVID-19 outbreak and was greater for benign than for malignant conditions. Onefourth of urological providers were deployed to assist with COVID-19 care. Many providers reported insufficient personal protective equipment and support from hospital administration. Patient summary: Coronavirus disease-19 (COVID-19) has led to significant delay in outpatient care and surgery in urology, particularly in regions with the most COVID-19 cases. A considerable proportion of urology health care professionals have been deployed to assist in COVID-19 care, despite the perception of insufficient training and protective equipment. (c) 2020 Published by Elsevier B.V. on behalf of European Association of Urology.
Keywords: Coronavirus disease-19; Severe acute respiratory syndrome coronavirus 2; Survey; Urology; Urological service; UroSoMe